Detailed Multiplex Analysis of SARS-CoV-2 Specific Antibodies in COVID-19 Disease - Brynjolfsson, Siggeir F.; Sigurgrimsdottir, Hildur; Einarsdottir, Elin D.; Bjornsdottir, Gudrun A.; Armannsdottir, Brynja; Baldvinsdottir, Gudrun E.; Bjarnason, Agnar; Gudlaugsson, Olafur; Gudmundsson, Sveinn; Sigurdardottir, Sigurveig T.; Love, Arthur; Kristinsson, Karl G.; et al. (Frontiers in Immunology, 2021)
A detailed understanding of the antibody response against SARS-CoV-2 is of high importance, especially with the emergence of novel vaccines A multiplex-based assay, analyzing IgG, IgM, and IgA antibodies against the receptor binding domain (RBD), spike 1 (S1), and nucleocapsid proteins of the SARS-CoV-2 virus was set up. The multiplex-based analysis was calibrated against the Elecsys® Anti-SARS-CoV-2 assay on a Roche Cobas® instrument, using positive and negative samples. The calibration of the multiplex based assay yielded a sensitivity of 100% and a specificity of 97.7%. SARS-CoV-2 specific antibody levels were analyzed by multiplex in 251 samples from 221 patients. A significant increase in all antibody types (IgM, IgG, and IgA) against RBD was observed between the first and the third weeks after diagnosis. Additionally, the S1 IgG antibody response increased significantly between weeks 1, 2, and 3 from diagnosis. Class switching appeared to occur earlier for IgA than for IgG. Patients requiring hospital admission and intensive care had higher levels of SARS-CoV-2 specific IgA levels than outpatients. These findings describe the initial antibody response during the first weeks of disease and demonstrate the importance of analyzing different antibody isotypes against multiple antigens and include IgA when examining the immunological response to COVID-19.